Improving Medication-taking Behavior and Blood Pressure in Hypertensive Patients Using the Stages of Change Model-based Health Education - SUN Xinying, GUO Yi, CHEN Ping, HE Chao (Zhongguo quanke yixue, 2022)
BackgroundHypertension in Chinese adults has been featured by high prevalence and low control rate recently. And medication-taking behavior is one of the important factors greatly affecting hypertension control in this group.ObjectiveTo assess whether stages of change model (SCM) based-health education could improve medication-taking behavior in hypertensive patients.MethodsThis cluster randomized controlled trial was conducted in six community health centers with comparable service population size and healthcare conditions selected from Shunyi District, Beijing during September 2016 to June 2018. By use of coin tossing, three of the community health centers were randomly assigned to an intervention group, and another three to a control group, from which, a total of 400 hypertensive patients were recruited, 206 from the intervention group and 194 from the control group, receiving three times of SCM-based health education, and usual management, respectively. Questionnaire surveys and blood pressure measuring were performed in all participants at baseline, 3, 6 and 12 months after intervention for understanding of their sociodemographic characteristics, medication-taking behavior, blood pressure level and barriers to medication adherence.ResultsThe patients who completed the 3-month, 6-month and 12-month follow-up numbered 375 (intervention: 202, control: 173) , 290 (intervention: 147, control: 143) and 263 (intervention: 134, control: 129) , respectively. After the end of the 12-month intervention, the percentage of patients in action and maintenance stages increased from 27.7% (57/206) to 60.5% (81/134) in the intervention group, while that in the control group decreased from 50.0% (97/194) to 38.9% (49/129) . Generalized estimating equations on action stage showed statistically significant inter-group differences in the interaction terms at group enrollment time and follow-up periods after controlling for other confounding variables (P<0.05) , that was intervention group×3-month follow-up〔OR (95%CI) =3.928 (2.628, 5.870) 〕, intervention group×6-month follow-up〔OR (95%CI) =3.651 (2.333, 5.712) 〕, and intervention group×12-month follow-up〔OR (95%CI) =4.133 (2.315, 7.377) 〕. Compared with the control group at baseline, the systolic blood pressure of the intervention group was continuously, significantly improved with the prolongation of intervention time at 3-month intervention〔b (95%CI) =-4.616 (-8.558, -0.675) 〕, at 6-month intervention〔b (95%CI) =-4.348 (-8.569, -0.127) 〕, and 12-month intervention〔b (95%CI) =-6.462 (-11.208, -1.716) , P<0.05〕, but the diastolic blood pressure of the intervention group achieved significant improvement only at the 3-month intervention〔b (95%CI) =-3.549 (-6.271, -0.827) , P<0.05〕.ConclusionThis research indicated that SCM-based healtheducation could effectively contribute to hypertension control via improvingthe medication-taking behavior of hypertension patients, and increasing the percentage of these patients entering the stages of action and maintenance.